Política Nacional de Transformación Digital: Aspectos centrales para la equidad digital - Chocobar Reyes, Marushka (Pontificia Universidad Católica del Perú, 2022)
For some years, Peru has started a determined push towards a national process of digital transformation that guarantees access to the opportunities of the digital environment for all people. This process has been accelerated by the demand for change and the disruption generated by the health crisis and, in turn, by the citizen’s decision to incorporate digital into their daily lives. The National Digital Transformation Policy emerges as a guiding document with the purpose of promoting digital citizenship, guaranteeing equitable and safe access to digital transformation and what determines the actions of the country’s Digital Agenda towards 2030. This article addresses those aspects of this Policy that will constitute the critical success factors to guarantee digital equity.

Desde hace algunos años, el Perú ha iniciado un decidido empuje hacia un proceso nacional de transformación digital que garantice el acceso a las oportunidades del entorno digital para todas las personas. Ese proceso ha sido acelerado por la exigencia de cambio y la disrupción generada por la crisis sanitaria y, a su vez, por la decisión ciudadana de incorporar lo digital en su día a día. La Política Nacional de Transformación Digital surge como un documento orientador con el propósito de impulsar la ciudadanía digital garantizando el acceso equitativo y seguro a la transformación digital y qué determina las acciones de la Agenda Digital del país hacia el 2030. El presente artículo aborda aquellos aspectos centrales de esta Política que constituirán los factores críticos de éxito para garantizar la equidad digital.
National Digital Transformation Policy: Fundamental aspects to guarantee digital equity
Keywords: Equidad Digital; Transformación Digital; Agenda Digital al 2030; Entorno Digital; Política nacional de Transformación Digital; Perú; Digital Equity; Digital Transformation; Digital Agenda 2030; Digital Environment; National Digital Transformation Policy; Peru; https://purl.org/pe-repo/ocde/ford#5.05.00